2018
DOI: 10.1016/j.vaccine.2017.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal carriage among a university student population – United States, 2015

Abstract: Objectives Several outbreaks of serogroup B meningococcal disease have occurred among university students in recent years. In the setting of high coverage of the quadrivalent meningococcal conjugate vaccine and prior to widespread use of serogroup B meningococcal vaccines among adolescents, we conducted surveys to characterize the prevalence and molecular characteristics of meningococcal carriage among university students. Methods Two cross-sectional oropharyngeal carriage surveys were conducted among underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 29 publications
3
45
0
2
Order By: Relevance
“…The numbers of adolescents smoking was lower than rates reported in a 2016 annual survey for 15 to 29 year olds in South Australia of 10.5% (95% CI, 7.8% to 13.2%), 18 and lower than other recent carriage studies in similar age groups. 2,19,20 Some carriage studies have reported a sharp increase in the prevalence of pharyngeal N. meningitidis during the first year Table 2. Proportion of Neisseria meningitidis pharyngeal carriage from oropharyngeal swab, at visit 1 (participants who were lost to follow up), visit 1 (returned for follow up swab), and combined total.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of adolescents smoking was lower than rates reported in a 2016 annual survey for 15 to 29 year olds in South Australia of 10.5% (95% CI, 7.8% to 13.2%), 18 and lower than other recent carriage studies in similar age groups. 2,19,20 Some carriage studies have reported a sharp increase in the prevalence of pharyngeal N. meningitidis during the first year Table 2. Proportion of Neisseria meningitidis pharyngeal carriage from oropharyngeal swab, at visit 1 (participants who were lost to follow up), visit 1 (returned for follow up swab), and combined total.…”
Section: Discussionmentioning
confidence: 99%
“…Associations with carriage at visit 1 reflected those reported previously in overseas studies, with attending one or more parties or bars in the last week, and kissing one or more persons in the last week both independently associated with carriage. 2,19,20,23 Of note, students that went out more than once a week and kissed one or more people had a carriage prevalence of 25%. The low numbers of participants who smoked, used e-cigarettes, or water pipes meant that little can be elucidated from these potential risk factors in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies that sampled only university students met the inclusion criteria. Six studies were cross-sectional studies (Aliyu and Olayinka, 2017;Bali et al, 2017;Rizek et al, 2016;Rodrigues et al, 2015;Rodriguez et al, 2014;Tryfinopoulou et al, 2016;Takahashi et al, 2016), six were repeat cross-sectional studies with a nested cohort (either intentional or unintentional) (Ala'aldeen et al, 2011;Breakwell et al, 2018;Durey et al, 2012;McNamara et al, 2017b;Oldfield et al, 2017;Soeters et al, 2017), two were cohort studies (Bidmos et al, 2011;Gilca et al, 2013), and one was a randomized controlled trial investigating the impact of vaccination on carriage (Read et al, 2014). The majority of studies were conducted in the region of the Americas (n = 6) or the European region (n = 6), and no study was identified from the Eastern Mediterranean region.…”
Section: University Studentsmentioning
confidence: 99%
“…Data collection. From February 2015 to March 2016, a total of ten rounds of cross-sectional carriage surveys were conducted at three U.S. universities (RI-1, RI-2, an OR) using standardized methods, as previously described (6,21,22) Fig. S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Additional work is under way to analyze the possible impact of mass vaccination on the carriage and acquisition of strains potentially covered by the vaccine, and this work will be published at a later date. A third carriage evaluation was conducted at another university in Rhode Island (RI-2), where no IMD outbreak or cases were reported (22) and no mass vaccination occurred. We sequenced isolates from these three carriage evaluations in order to describe within-host genetic changes in individuals carrying N. meningitidis at multiple time points, elucidate the meningococcal carriage population structure, and compare closely related carriage and outbreak isolates.…”
mentioning
confidence: 99%